Deleterious variants in TAF7L cause human oligoasthenoteratozoospermia and its impairing histone to protamine exchange inducing reduced in vitro fertilization - Bai, Haowei; Sha, Yanwei; Tan, Yueqiu; Li, Peng; Zhang, Yuxiang; Xu, Junwei; Xu, Shuai; Ji, Zhiyong; Wang, Xiaobo; Chen, Wei; Zhang, Jianxiong; Yao, Chencheng; et al. (Frontiers in Endocrinology, 2023)
Oligoasthenoteratozoospermia(OAT) is a major cause of infertility in males. However, a large number of OAT-affected cases remain largely unknown. In this study, Whole-exome sequencing (WES) of 725 idiopathic OAT patients was performed. Four X-linked hemizygous deleterious variants of TAF7L were identified in five probands (0.68%,5/725). These four variants in TAF7L were missing in genome databases of the human control population and were anticipated with deleterious effect through in silico analysis. These five probands with TAF7L variants didn't get clinical pregnancy using ejaculated spermatozoa, three of them chose donor's sperm for ICSI treatment, but one proband (family 1, M1: II-1) got successful clinical pregnancy using spermatozoa of testes. We also microinjected ejaculated spermatozoa into mouse oocytes to demonstrate that patients with TAF7L mutations have significantly reduced in vitro fertilization. Subsequently we identified that its impairing histone-to-protamine exchange affected the chromatin compaction of sperm head, which accounted for the low fertilization of ejaculated spermatozoa derived from probands. The results of this study will help in genetic counselling and treatments of male infertility.